2017
DOI: 10.2106/jbjs.17.00022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity on Pain and Functional Recovery Following Total Knee Arthroplasty

Abstract: Background: While obesity may be a risk factor for complications following total knee arthroplasty, data remain sparse on the impact of the degree of obesity on patient-reported outcomes following this procedure. Our objective was to determine the extent to which obesity level affects the trajectory of recovery as well as patient-reported pain, function, and satisfaction with surgery following total knee arthroplasty. Methods: We followed a cohort of patients who underwent total knee arthroplasty at 1 of 4 med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
69
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 40 publications
(48 reference statements)
6
69
0
3
Order By: Relevance
“…Numerous studies have focused on the influence of obesity on the morbidity and clinical outcomes of TKA, probably because there are few underweight patients with osteoarthritis in Western countries. 1,3,6,[29][30][31] However, many patients with osteoarthritis are underweight in Asia, and being underweight in the elderly patients could be predictor of functional disability, so it is also important to determine the clinical outcomes of underweight elderly patients who have TKA. This is the first study to assess the effect of being underweight on clinical and radiologic outcomes of TKA.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have focused on the influence of obesity on the morbidity and clinical outcomes of TKA, probably because there are few underweight patients with osteoarthritis in Western countries. 1,3,6,[29][30][31] However, many patients with osteoarthritis are underweight in Asia, and being underweight in the elderly patients could be predictor of functional disability, so it is also important to determine the clinical outcomes of underweight elderly patients who have TKA. This is the first study to assess the effect of being underweight on clinical and radiologic outcomes of TKA.…”
Section: Discussionmentioning
confidence: 99%
“…Период реабилитации не отличался по результатам от такового у пациентов с нормальным ИМТ, что коррелирует с данными других исследователей [13][14][15].…”
Section: Discussionunclassified
“…Unlike individuals in the Lenguerrand et al study (21), who did not show any improvement after 3 months, participants in 2 other studies (29,31) experienced a small improvement up to 1 year ( Figure 2B). Over 2 years, all patients showed improvement in physical function, whatever their BMI (27). During 5 years postoperatively, Riddle et al (25) found WOMAC scores improved during the first 3 years, then WOMAC scores showed mildly accelerated worsening.…”
Section: Studies Describing the Mean Course Of Clinical Outcomes And mentioning
confidence: 90%